Identification of genomic regions affecting nitrogen excretion intensity in Brown Swiss dairy cows - Žan Pečnik; Daša Jevšinek Skok (Animal Biotechnology, 2024)
Dairy cows with a lower nitrogen excretion intensity (Nexi) excrete less nitrogen, ammonia (NH3) and nitrous oxide (N2O), a highly potent greenhouse gas (GHG), per kg of milk produced and therefore represent a lower environmental impact while maintaining food security. To date, the genomics background of Nexi is unknown. Here we performed a genetic association study, overlap analysis and functional enrichment analysis for Nexi in 875 genotyped dairy cows with 2,147 lactations from 200 herds. We identified 1456 single nucleotide polymorphisms (SNPs) that significantly affect Nexi. We found 140 SNPs overlapping with 148 protein-coding genes. The MAN1A1 gene is a strong candidate gene for Nexi. Genotype CC of rs42786248, the most significantly associated SNP located in the MAN1A1 gene, had higher Nexi than genotypes AA (p < 0.001) and AC (p < 0.001). We identified 33 genes involved in biological processes related to nitrogen metabolism. Our results form the basis for further research on the genomics background of Nexi. The identified SNPs serve as potential targets for selective breeding programs, aimed at reducing Nexi and associated NH3 and N2O emissions in cattle production, thus contributing to more environmentally sustainable milk production.